Quantifying long-term impacts of COVID-19 and oil price shocks in a Gulf oil economy - Shehabi, M (Oxford Institute for Energy Studies, 2021)
The COVID-19 pandemic had been particularly deleterious on economies that export commodities with volatile prices. The effects have been visible even in the relatively wealthy yet hydrocarbon-overdependent Gulf Cooperation Council (GCC) states. Notwithstanding differences among them, GCC states faced adverse effects of the pandemic along with expanded economic stimulus packages and a simultaneous large drop in oil export revenue and government budgets. These dynamics are problematic to the extent that they affect current economic development and become enduring and foundational if the energy transitions accelerate to meet the Paris Agreement targets. In the context, this paper investigates the following questions: (a) what are the long-term impacts of oil price declines and COVID-19 associated shocks on Gulf economies?; and (b) what lessons can be drawn from the pandemic and domestic policy responses to it for the future management of the accelerating energy transitions and enhancing economic sustainability?